Influence of overcommitment on the quality of life and on climacteric symptoms in nursing professionals - Dinah Belém; Carlos Rodrigues da Silva Filho; Alessandro Ferrari Jacinto; Alex Bacadini França; Lucieni Oliveira Conterno (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To describe the general characteristics of nursing professionals and assess the influence of overcommitment on perceived climacteric symptoms and on the quality of life of nursing professionals. Method: A cross-sectional, analytical study of 152 nursing auxiliaries and assistants aged 40 years or older was conducted at 3 hospitals in the interior of São Paulo state. Sociodemographic data were collected and the Blatt-Kupperman Menopausal Index, Women´s Health Questionnaire, Medical Outcome Study 36-item Short Form Health Survey and Effort-Reward Imbalance were applied in 2017. A descriptive analysis was performed and network analysis was carried out. Results: Participants had a mean age of 50.23 years (SD ±7.1). Group 1 comprising 61 (40.1%) women with overcommitment had poorer quality of life as well as more severe climacteric symptoms. Conclusions: Presence of overcommitment seems to influence the negative perception of climacteric symptomatology and quality of life.